Epidemiology of Pediatric Bite/Sting Injuries. One-Year Study of a Pediatric Emergency Department in Israel. (2006) - Hemmo-Lotem, Michal; Barnea, Yoav; Jinich-Aronowitz, Claudia; Endy-Findling, Liri; Leshem, David; Zaretski, Arik; Merrick, Joav
Abstract : Animal bite/sting injuries are a known source of morbidity with a significantly higher incidence among children who are most often bitten in the face, head, and neck. The objective of this study was to provide a better understanding of bite/sting injuries treated at the pediatric emergency department in order to guide preventive efforts.The sociodemographic, epidemiological, and clinical data on all bite/sting injuries treated in one representative pediatric emergency department in Israel over a 1-year period were retrieved and analyzed. Two hundred of the 9, 309 pediatric trauma cases treated in the emergency department were bite/sting injuries (2.1%). Non-Jewish patients were under-represented in this subgroup. The majority of patients were males (61.5%). Age distribution from 0–12 years was fairly even, except for an unexplained peak at 8 years. Dogs inflicted 56%, cats 11%, and hornets 9.5% of the injuries. Limbs were affected in 64% and the head and neck in 27%. Specialists, mostly plastic surgeons, were consulted in 42 cases (21%). The incidence rate for hospitalization (7%) was similar to that seen in other types of injuries. Children with scorpion or hornet stings and young age were more likely to be hospitalized. Preventive and educational aspects are discussed.